2008
DOI: 10.1038/labinvest.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression in repopulating mesangial cells promotes their proliferation

Abstract: We investigated whether the intermediate filament protein and neural stem cell marker nestin characterizes the glomerular progenitor/reserve cell population immigrating the glomerulus after mesangial cell (MC) injury in the rat (antiThy1 nephritis). Nestin expression was investigated by immunohistochemistry and real-time PCR during anti-Thy1 nephritis. Migration and proliferation assays were used to characterize the function of nestin in isolated MCs after nestin knockdown by siRNA. After MC injury during anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 44 publications
5
44
0
2
Order By: Relevance
“…Consequently, experiments using 10 nM siRNA were shown. Downregulation of transgelin was evaluated by western-blot analysis as previously described 18 and cells were tested in proliferation and migration assays.…”
Section: Transfection With Transgelin Sirnamentioning
confidence: 99%
“…Consequently, experiments using 10 nM siRNA were shown. Downregulation of transgelin was evaluated by western-blot analysis as previously described 18 and cells were tested in proliferation and migration assays.…”
Section: Transfection With Transgelin Sirnamentioning
confidence: 99%
“…Despite the plethora of data supporting the premise that nestin expression identified a stem cell phenotype, recent studies have detected the intermediate filament protein in numerous non-stem cell populations during physiological growth and pathological remodeling. Nestin was highly expressed in developing skeletal myofibers and downregulated following maturation, upregulated in endothelial cells during reparative angiogenesis, and induced in mesangial cells following injury and in scar myofibroblasts and cardiac myocyte-like cells bordering the peri-infarct/infarct region of the ischemically damaged rodent and human heart (1,3,4,7,9,11,24,25,31,32). However, in contrast to neural progenitor/stem cells, expression of the intermediate filament protein in skeletal myofibers and endothelial cells was driven by the first intron of the nestin gene (1,42,43).…”
mentioning
confidence: 99%
“…However, in contrast to neural progenitor/stem cells, expression of the intermediate filament protein in skeletal myofibers and endothelial cells was driven by the first intron of the nestin gene (1,42,43). Biologically, nestin expression was reported to play a seminal role in cell proliferation (4,9,37,38).Vascular remodeling is a hallmark feature of hypertension, characterized in part by the proliferation and hypertrophy of vascular smooth muscle cells (13). A recent study reported that a subpopulation of vascular smooth muscle cells residing in the normal rat aorta expressed the intermediate filament protein nestin and was actively engaged in the cell cycle (27).…”
mentioning
confidence: 99%
“…Currently, the regular methodology is to use a combination of FGF-2 and EGF co-factors to culture NSCs in vitro (9)(10)(11)(12). In this study, we used the same method to culture NSCs and confirmed the cell identify using immunohistochemical staining for nestin, a protein that disappears along with the differentiation and maturation of the neural epithelium (13)(14)(15)(16). CaM has been proven to be a versatile Ca 2+ -binding protein and exists in neural cells in a large quantity (17)(18)(19).…”
Section: Discussionmentioning
confidence: 89%